Analisis Yuridis Pemberian Justice Collaborator Pada Pelaku Tindak Pidana Narkotika : Studi di Kejaksaan Negeri Karo - Pola Martua Siregar; Madiasa Ablisar; Muhammad Ekaputra; Edi Yunara (USU LAW JOURNAL, 2019)
Abstract. Disclosure and verification of the perpetrators of narcotics crimes requires the provision of justice collaborators in resolving the narcotics crime. This was done so that law enforcement officials, especially in the Karo District Prosecutor's Office were able to uncover an organized narcotics crime in Tanah Karo. Therefore, it is necessary to examine the need for Justice Collaborators in an effort to uncover the occurrence of certain criminal acts, legal arrangements regarding justice collaborator in Indonesia and the application of justice collaborators to perpetrators of narcotics crimes in the Karo District Prosecutor's Office.   Keywords: narcotics crime, justice collaborator and prosecutor's office